Enhancing Students’ Conceptual Understanding of Elasticity Through IoT Based Real Time Multiple Representations: A Quasi Experimental Study - Ahmad Syarif Hidayatuloh; Sulhadi Sulhadi; Ani Rusilowati; Andi Fadllan (Universitas Negeri Semarang, 2026)
The students have had problems in forming a proper understanding of the concept of elasticity in terms of integrating numbers, graphs, and mathematics in understanding the relationship between force and deformation. This study was designed to investigate the effect of IoT-based real-time representation on the conceptual understanding of elasticity. A quasi-experimental design was used by taking a non-equivalent control group from eleventh graders. While the experimental group went through an IoT-based practicum in which they were able to visualize real-time numerical and graphical representations, the control group followed the standard practice in the laboratory. The test of conceptual understanding of the students involved the use of a diagnostic reasoning instrument, and the analysis of covariance was applied in analyzing the gathered data. The results showed that the use of IoT-based representation improved students’ conceptual understanding of elasticity more than traditional classroom learning.